Cultivo de la microalga Scenedesmus Obliquus var. Dimorphus (TURPIN) para la obtención de biomasa y lípidos. - Mercado Tupiño, Estefanía (2016)
Microalgae have proved to be the Source of Energy More Economic for Production of biodiesel. In addition to reducing Carbon Dioxide, also they have a high growth rate in a short time and need less space compared to other crops. The aim of this thesis was to determine how a culture medium for Scenedesmus obliquus var. dimorphus (Turpin) is obtained a high amount of biomass and a high oil content. Initially, the experimental work consisted in obtaining pure strain Scenedesmus dimorphus (14 mL). Then, scaling up culture developed as follows is performed: 100 mL, 250 mL, 500 mL, 1L, 2L y 5L, to determine the growth curves by S. dimorphus cell count using the Neubauer chamber, obtaining the following results: 3 '451,500 cells in 120 hours (Bayfolan Forte), 2'472,500 cells 192 hours (BG-11) and 327,500 cells in 96 hours (Guillard). Being Forte Bayfolan that had the highest peak in increasing the population density of S. dimorphus, and in the last two culture media (BG-11 and Guillard) and in the last two culture media (BG11 and Gillard) had a high pollution what couldn´t continue grow in scale. Concluding that Bayfolan forte had better result. After that, 5 harvest was performed, so I chose the flocculation method with aluminum sulfate Al2(SO4)3 and subsequently, for the extraction of oils, the dry biomass (36.5 g) then with solvent extraction in hexane/isopropanol, and was obtained a totally of 30 mL of lipid. Finally, statistical part was tested using different methods, such as: Anova, Tukey and T. Student for the validity of the hypothesis.